The Mother of Rufus and Paul in Romans 16 - Peters, Janelle (Journal for interdisciplinary biblical studies (JIBS), 2022)
Rufus’s mother features in Paul’s concluding list of church leaders such as Phoebe in Romans 16. Paul calls her his own mother. I argue that Rufus’s mother’s inclusion indicates higher status and influence within the Pauline house-churches, building on Elmer’s notion of corporate Pauline authorship.